Low-Complexity SC-FDE Techniques for Massive MIMO Schemes With Low-Resolution ADCs - Guerreiro, Joao; Dinis, Rui; Montezuma, Paulo (IEEE transactions on communications, 2019)
Massive multiple-input multiple-output (mMIMO) systems are very important for 5G since they are one of the main enablers of the targeted huge capacity gains. On the other hand, the power consumption at the mobile terminals should be as low as possible, making single-carrier waveforms, such as single carrier with frequency-domain equalization (SC-FDE), particularly interesting, since the transmit signals can have a low peak-to-average power ratio (PAPR), allowing a highly efficient power amplification. However, the combination of mMIMO systems with SC-FDE modulations gives rise to implementation difficulties at the receiver side. On one hand, the equalization procedure should avoid matrix inversions, but this might lead to performance degradation. On the other hand, low-resolution analog-to-digital converters (ADCs) should be employed in each receive branch to reduce the implementation complexity, which might lead to severe nonlinear distortion effects. In this work, we study analytically the performance of mMIMO systems based on SC-FDE schemes employing low-complexity, iterative FDE receivers, and low-resolution ADCs. It is shown that the performance degradation associated to low-resolution ADCs can be tolerable if the number of receive antennas is larger than the number of transmit antennas, even when low-complexity FDE receivers are employed.